Legal Liability of Marketplace Platform Operators for Product Description Violations Under Indonesian Consumer Protection Law - Afifah, Afifah Nuranti Putri; Rahmatiar, Yuniar; Abas, Muhammad; Sanjaya, Suyono (Jurnal Cakrawala Hukum, 2025)
This study examines the legal liability of Shopee as a marketplace platform operator under Regulation of the Minister of Trade Number 31 of 2023, and evaluates the extent to which Law Number 8 of 1999 on Consumer Protection (UUPK) delivers genuine legal certainty for consumers harmed by product description violations. A normative juridical method is employed, combining statutory, conceptual, and case approaches. The study finds that Shopee's liability mechanism under Article 30 of Permendag No. 31 of 2023 is structurally incomplete: enforcement depends solely on opaque algorithmic moderation without independent oversight, and the Regulation imposes no direct liability on the platform for harm its system failed to prevent. As a PPMSE controlling fees, escrow, and dispute resolution, Shopee qualifies as a business actor under Article 1(3) of the UUPK and cannot claim immunity as a neutral intermediary. Legal certainty remains formally guaranteed but practically unrealised: Shopee's unboxing video requirement violates Article 22's reversed burden of proof and Article 18's prohibition on unfair standard clauses, while BPSK is structurally inaccessible to ordinary online consumers. The study recommends extending the reversed burden of proof to civil dispute proceedings, prohibiting platform-imposed evidentiary barriers, and mandating transparent reporting on internal dispute resolution outcomes.